Parental Practices for the Prevention of Risk Situations: Children and Young People’s Perceptions Within the Adélia Project Framework - Margarido, Cristóvão; Duarte Santos, Rui; Silva, Tânia; Carreira, Elisabete; Mergarido, Emanuel (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2022)
Positive parenting is a reality to be achieved through formal and informal protection networks, with the participation of children and young people. This article aims to understand the perceptions of children and young people about parenting practices experienced in their daily lives. The research is based on a quantitative approach, from data collected through a questionnaire survey of 954 children and young people in the Central Region of Portugal. The results show perceptions of parental dynamics in different dimensions of their daily lives: play and leisure; participation and citizenship; security and protection; health; education; and other matters of personal life.
Keywords: positive parenting; children and young people; Adelia Project